Epithelioid Osteoblastoma of Scaphoid Bone-A Case Report and Review of Literature - Pradnya K. Ladkat; Kiran M. Ladkat; Yasmeen Khatib; Ramvilas Nag (Medical Journal of Dr. D.Y. Patil Vidyapeeth)
Osteoblastoma of the scaphoid is a rare cause of wrist pain and swelling with about 10 cases reported in English literature. We present a case of epithelioid variant of this tumor in this unusual location which has not yet been reported. A 22-year-old male presented with complaints of pain and swelling of the right wrist which was initially treated as an infection with no relief. Finally, curettage was performed and a diagnosis of osteoblastoma was made on histopathology. We present this case for its rarity, and diagnostic difficulty and to highlight the need of histopathology for its diagnosis and treatment.